Exploring the Shift from Employee Engagement to Employee Experience in Improving Organizational Performance: A Study of Hospitality Sector - et. al., Dr. Sushmita Goswami, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this study is to explore the various factors of employee engagement and employee experience and measure the effect of employee experience and employee engagement on organisational performance. Descriptive research design was used in this study. Formulated hypothesis were tested by sample based methods, using questionnaire and convenience sampling method. A sample size of 223 employees from different hospitality sector organisations in Delhi and North central region (NCR) was analyzed using exploratory factor analysis using SPSS 22 and then regression analysis was carried out to test the proposed hypothesis. Findings of the study indicates that employee engagement and employees experience has played significant role in improvement in the Brand Equity of hospitality organisations in Delhi and North central region (NCR). It is to note that workers with high experience scores are more likely to report high levels of work performance as compared to highly engaged employee. The concept of customer experience has been applied successfully in enhancing employee engagement which will be useful in enhancing marketability of the product; it is a just beginning and management must explore the new and innovative mean to shift their strategies from employee engagement to employee experience in gaining desired outcome